Microstructure and phase composition evolution of silicon-hafnia feedstock during plasma spraying and following cyclic oxidation. (1st August 2021) - Bakan, Emine; Sohn, Yoo Jung; Vaßen, Robert
Abstract: In this work, silicon–hafnia (Si-HfO2, 80/20 mol. %) feedstock was plasma sprayed for Environmental Barrier Coating bond coat application. In the as-sprayed coating, hafnium disilicide (HfSi2 ), HfO2 tetragonal (t), and cubic (c) phases with a total volume of 20 % were detected together with Si and HfO2 monoclinic (m). The temperature-dependent evolution of these phases was analyzed and paired with microstructural observations. It was found that above 700 °C, HfSi2 oxidizes and HfO2 (t) and (c) transforms into (m) polymorph. Up to this temperature, as-sprayed coating showed a non-linear expansion behavior. Estimated volume expansion at 750 °C was 3.6 % based on dilatometry measurement. The primary and secondary mechanisms leading to the expansion in the coating were identified as oxidation of HfSi2 and polymorphic phase transitions in HfO2, respectively. As a consequence of the volume expansion, the coating was extensively cracked during cyclic oxidation and hence not protective anymore. After 100 h at 1300 °C, the volume fraction of oxidation product SiO2 was significant in the coating (0.34), while HfO2 was largely consumed (0.1) in the formation of HfSiO4 (0.56). This result suggested that reversible α↔β phase transitions in SiO2 -cristobalite could be another factor contributing to the cracking in the coating during cyclic oxidation. Graphical abstract: Image, graphical abstract